Pengaruh gadget pada proses belajar anak sekolah dasar - Ita'ufaidilah, Salvi (Maliki Interdisciplinary Journal, 2024)
To produce young generation candidates for a golden Indonesia, children must not be addicted to gadgets. Gagets have provided a means of playing that really attracts children’s nattention. The main problem is that gadgets are tools in a one way communication system, so that feedback given to children is not visible and their language development is hampered. Children will also be passive when invited to communicate. The methodology of this research is a literature review. A literature review research approach includes reading and evaluating previous works that have been written on the subject being discussed. Playing with gadgets has many negative effects, for example addiction, disruption of brain function (Pre Frontal Cortex), disruption of childrens emotional development, delays in cognitive development, and health problems. Therefore, parents have a full role in children’s development. A child at elementary school level must be continuously monitored by his parents. Because, in this era, most children’s playmates are not their parents of perrs, but gadgets.